Жангар тууль дахь дом шившлэг: Magic in Janggar epic - Г., Нандинбилиг (Mongolian Studies, 2023)
Analyzing the instances of magic in the Janggar epic, one finds there are classical details of primitive magic apart from spirit belief also peculiar magic of animist belief before religious one. According to J.Frazer, traditions of both sympathetic and contagious magic can be found—peculiarly—in the Janggar epic. As sympathetic magic relies on similarity, spirit itself becomes magic object; it does not receive any help from spirit. Some motives can be occurred that relying on contact or ‘contagion’.